Microvascular perfusion 1 week and 6 months after myocardial infarction by first-pass perfusion cardiovascular magnetic resonance imaging. Issue 12 (27th June 2006) - Bodí, V; Sanchis, J; López-Lereu, M P; Núñez, J; Sanz, R; Palau, P; Gómez, C; Moratal, D; Chorro, F J; Llácer, À
Abstract : Objective: To characterise the evolution of myocardial perfusion during the first 6 months after myocardial infarction by first-pass perfusion cardiovascular magnetic resonance imaging (CMR) and determine its significance. Design: Prospective cohort design. Setting: Single-centre study in a teaching hospital in Spain. Patients: 40 patients with a first ST-elevation myocardial infarction, single-vessel disease and thrombolysis in myocardial infarction (TIMI) grade 3 flow (stent in 33 patients) underwent rest and low-dose dobutamine CMR 7 (SD 1) and 184 (SD 11) days after infarction. Microvascular perfusion was assessed at rest by visual assessment and quantitative analysis of first-pass perfusion CMR. Of the 640 segments, 290 segments subtended by the infarct-related artery (IRA) were focused on. Results: Both 1 week and 6 months after infarction, segments with normal perfusion showed more wall thickening, contractile reserve and wall thickness, and less transmural necrosis, p <0.05 in all cases. Of 76 hypoperfused segments at the first week, 47 (62%) normalised perfusion at the sixth month. However, 42 segments (14% of the whole group) showed chronic abnormal perfusion; these segments showed worse CMR indices in the late phase (p<0.05 in all cases). Conclusions: In patients with an open IRA, more than half of the segments with abnormal perfusion at the first week are normally perfused after six months. First-pass perfusion CMR shows that in a small percentage of segments, abnormal perfusion may become a chronic phenomenon—these areas have a more severe deterioration of systolic function, wall thickness, contractile reserve and the transmural extent of necrosis.